2017
DOI: 10.1097/ta.0000000000001488
|View full text |Cite
|
Sign up to set email alerts
|

Relative device stability of anterior versus axillary needle decompression for tension pneumothorax during casualty movement

Abstract: Therapeutic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Aside from elasticity, catheters can also be dislodged during transport. 9 This likely means that some of the catheters we identified as outside the pleural space were, at one point during transport, properly placed, and our result of 76 per cent may overestimate the failure rate. The 39 per cent of our patients who had no pneumothorax at all likely underestimates the true failure rate because many patients had a TT placed before CT scans because of a concerning clinical condition and a report of a prehospital ND.…”
Section: Limitationsmentioning
confidence: 82%
See 1 more Smart Citation
“…Aside from elasticity, catheters can also be dislodged during transport. 9 This likely means that some of the catheters we identified as outside the pleural space were, at one point during transport, properly placed, and our result of 76 per cent may overestimate the failure rate. The 39 per cent of our patients who had no pneumothorax at all likely underestimates the true failure rate because many patients had a TT placed before CT scans because of a concerning clinical condition and a report of a prehospital ND.…”
Section: Limitationsmentioning
confidence: 82%
“…16 Not only does ND at the 2nd ICS MCL seem to have a significant failure rate, identification of the 2nd ICS MCL is difficult, 17 and associated with serious complications. [18][19][20][21] Catheter placement at the 5th ICS AAL seems to be more stable 9 and easier to teach. 3…”
Section: Discussionmentioning
confidence: 99%
“…However, this was a cadaveric study involving a select BMI of 24 kg/m 2 , which does not represent our patient population. 17 In addition to identifying the proper location, an appropriate needle length is also crucial for a successful catheter placement. Givens and colleagues 18 challenged the previous recommendations of a 5 cm angiocatheter.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they concluded that the fourth/fifth ICS-AAL may be a better option in patients with a suspected thicker chest wall or in patients in which a prior NT attempt had failed. 16 Furthermore, Leatherman and colleagues 17 noted that the fifth ICS-AAL was most stable for combat casualty transport. However, this was a cadaveric study involving a select BMI of 24 kg/m 2 , which does not represent our patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation